Pengaruh Pemadatan Tanah Gambut terhadap Sifat Fisik di Lokasi Kebun Raya Sriwijaya Sumatera Selatan - Maryani, Sri; Novriadhy, Dian; Karenina, Tili (Seminar Nasional Lahan Suboptimal, 2024)
Maryani, S., Novriadhy, D., & Karenina, T. (2024). The effect of peat soil compaction on physical properties at the Sriwijaya Botanical Gardens, South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 878–885). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The physical characteristics of the soil at each location are always different, especially for land that contains peat. The Sriwijaya Botanical Gardens of South Sumatra is a botanical garden on peat land with five functions, namely plant conservation, research, education, tourism and environmental services. These various functions will result in soil compaction which also affects the physical properties of peat soil, so research is needed to determine the effect of peat land compaction on the physical properties of the soil at the Sriwijaya Botanical Gardens of South Sumatra for planning the management of this land in the future. This research was conducted at the Sriwijaya Botanical Gardens in Bakung Village, Indralaya Utara District, Ogan Ilir Regency, South Sumatra Province with a peat land type. Soil sampling was carried out using a soil sample ring at a soil depth of between 0-20 cm. The sample points were determined as many as 20 points on a land area of 100 hectares. The parameters of the physical characteristics of the soil observed were bulk density, soil pore space and water content. Observations of the physical characteristics of the soil were carried out at the Laboratory of the Soil Department, Sriwijaya University. The results of the study showed that the physical characteristics at several soil sampling locations in the peatlands of the Sriwijaya Botanical Gardens of South Sumatra varied, influenced by the function of the land before and after development, the depth of the peat, and the distance of the location from the canal. The physical characteristics of the soil bulk density value at the location ranged from 0.15 to 0.38; the soil pore space obtained with an average value of 93.68% and the saturated water content ranged from 66.68% - 98%). It is hoped that the identification of the physical characteristics of this land can be used as a reference material in the planning and management of peatlands at this location in the future.